Overview of modern aspects of the introduction of unmanned aviation in various spheres of the economy - Boiko, S.; Бойко, С.; Rog, O.; Рог, О.; Vasin, I.; Васін, І. (Perspectives of contemporary science: theory and practice: The 8th International scientific and practical conference (Lviv, Ukraine, September 16-18, 2024). - Lviv, 2024. - P. 166-171, 2024)
Метою даної роботи є розгляд комплексу проблем і особливості впровадження безпілотної авіації в різні сфери народного господарства.

The purpose of this work is to consider a complex of problems and features of the introduction of unmanned aerial vehicles in various spheres of the national economy.

Целью данной работы является рассмотрение комплекса проблем и особенностей внедрения беспилотных летательных аппаратов в различные сферы народного хозяйства.
Keywords: БПЛА; безпілотні літальні апарати; сфера народного господарства; оператор; UAVs; unmanned aerial vehicles; sphere of national economy; operator; беспилотные летательные аппараты; сфера народного хозяйства